Martin Luther and Buddhism : aesthetics of suffering - Chung, Paul S., 1958- (Princeton theological monograph series Martin Luther and Buddhism, 2008)
Martin Luther and Buddhism: Aesthetics of Suffering carefully traces the historical and theological context of Luther's breakthrough in terms of articulating justification and justice in connection to the Word of God and divine suffering. Chung critically and constructively engages in dialogue with Luther and with later interpreters of Luther such as Barth and Moltmann, placing the Reformer in dialogue not only with Asian spirituality and religions but also with an emerging global theology of religions.